Pediatric Surgery and Anesthesia in Low-Middle Income Countries: Current Situation and Ethical Challenges - Pulvirenti, Rebecca; Gortan, Marianna; Cumba, Dioniso; Gamba, Piergiorgio; Tognon, Costanza (Frontiers in Pediatrics, 2022)
Low-middle income countries (LMICs) are currently experiencing an important population growth, leading to a substantial raise in the number of children living in those areas. As a consequence, the existing gap between the need for surgical and anesthetic care and the available therapeutic options will increase. To overcome this, an improvement in the available expertise, infrastructures, and supplies will be mandatory. The implementation of educational and training programs for local healthcare providers should be a top priority. Alongside, the population's awareness on the necessity to seek for medical care should be deployed, together with an eased access to health facilities. Based on the existing literature and our 20-years’ experience in humanitarian missions, our article aims to investigate the status of pediatric surgery in LMICs, and the role of western aids in the implementation of this ever-increasing field of expertise.